Engineering Hydrogels with Affinity-Bound Laminin as 3D Neural Stem Cell Culture Systems - Barros, D (2019)
Laminin incorporation into biological or synthetic hydrogels has been explored to recapitulate the dynamic nature and biological complexity of neural stem cell (NSC) niches. However, the strategies currently explored for laminin immobilization within three-dimensional (3D) matrices do not address a critical aspect influencing cell-matrix interactions, which is the control over laminin conformation and orientation upon immobilization. This is a key feature for the preservation of the protein bioactivity. In this work, we explored an affinity-based approach to mediate the site-selective immobilization of laminin into a degradable synthetic hydrogel. Specifically, a four-arm maleimide terminated poly(ethylene glycol) (PEG-4MAL) macromer was functionalized with a mono-PEGylated recombinant human N-terminal agrin (NtA) domain, to promote high affinity binding of laminin. Different NtA concentrations (10, 50 and 100 M) were used to investigate the impact of NtA density on laminin incorporation, hydrogel biophysical properties, and biological outcome. Laminin was efficiently incorporated for all the conditions tested (laminin incorporation > 95%), and the developed hydrogels revealed mechanical properties (average storage modulus (G’) ranging from 187 to 256 Pa) within the values preferred for NSC proliferation and neurite branching and extension. Affinity-bound laminin PEG-4MAL hydrogels better preserve laminin bioactivity, compared to unmodified hydrogels and hydrogels containing physically entrapped laminin, being this effect dependent on NtA concentration. This was evidenced by the 10 M NtA-functionalized PEG-4MAL gels incorporating laminin that support enhanced human NSC proliferation and neurite extension, compared to the latter. Overall, this work highlights the potential of the proposed engineered matrices to be used as defined 3D platforms for the establishment of artificial NSC niches and as extracellular matrix-mimetic microenvironments to support human NSC transplantation.